Multi-instrument sounding of a Jovian thunderstorm from Juno - Shawn R. Brueshaber; Zhimeng Zhang; John H. Rogers; Gerald Eichstädt; Glenn S. Orton; Davide Grassi; Leigh N. Fletcher; Cheng Li; Shinji Mizumoto; Alessandro Mura; Fabiano Oyafuso; Ramanakumar Sankar; et al. (Icarus, 2025)

High promiscuity among females of the invasive pest species Drosophila suzukii - Simone Puppato; Giulia Fiorenza; Davide Carraretto; Ludvik Marcus Gomulski; Giuliano Gasperi; Carlos Caceres; Alberto Grassi; Maria Vittoria Mancini; Antonio De Cristofaro; Claudio Ioriatti; Robin Guilhot; Anna Rodolfa Malacrida (Molecular Ecology, 2023)
Drosophila suzukii (Matsumura, 1931), the spotted‐wing drosophila, is a highly invasive fruit fly that spread from Southern Asia across most regions of Asia and, in the last 15 years, has invaded Europe and the Americas. It is an economically important pest of small fruits such as berries and stone fruits. Drosophila suzukii speciated by adapting to cooler, mountainous, and forest environments. In temperate regions, it evolved seasonal polyphenism traits which enhanced its survival during stressful winter population bottlenecks. Consequently, in these temperate regions, the populations undergo seasonal reproductive dynamics. Despite its economic importance, no data are available on the behavioural reproductive strategies of this fly. The presence of polyandry, for example, has not been determined despite the important role it might play in the reproductive dynamics of populations. We explored the presence of polyandry in an established population in Trentino, a region in northern Italy. In this area, D. suzukii overcomes the winter bottleneck and undergoes a seasonal reproductive fluctuation. We observed a high remating frequency in females during the late spring demographic explosion that led to the abundant summer population. The presence of a high degree of polyandry and shared paternity associated with the post‐winter population increase raises the question of the possible evolutionary adaptive role of this reproductive behaviour in D. suzukii .

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Not the one, but the only one: about Cannabis cryptic virus in plants showing ‘hemp streak’ disease symptoms - Laura Righetti; Roberta Paris; Claudio Ratti; Matteo Calassanzio; Chiara Onofri; Davide Calzolari; Wulf Menzel; Dennis Knierim; Gianmaria Magagnini; Daniela Pacifico; Gianpaolo Grassi (European Journal of Plant Pathology, 2018)